2017
DOI: 10.1002/adma.201702770
|View full text |Cite
|
Sign up to set email alerts
|

On‐Demand Reconfiguration of Nanomaterials: When Electronics Meets Ionics

Abstract: Rapid advances in the semiconductor industry, driven largely by device scaling, are now approaching fundamental physical limits and face severe power, performance, and cost constraints. Multifunctional materials and devices may lead to a paradigm shift toward new, intelligent, and efficient computing systems, and are being extensively studied. Herein examines how, by controlling the internal ion distribution in a solid‐state film, a material's chemical composition and physical properties can be reversibly reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
154
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(155 citation statements)
references
References 225 publications
(445 reference statements)
0
154
0
1
Order By: Relevance
“…Fundamental device and materials characterizations have shown that the reconfiguration in memristors is typically driven by internal ion redistribution 3,5 . Specifically, the storage layer in a memristor is typically a few nanometres thick, thus even a moderate voltage drop across it can create a large enough electric field to drive the ionic processes to alter the ionic configuration of the material.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Fundamental device and materials characterizations have shown that the reconfiguration in memristors is typically driven by internal ion redistribution 3,5 . Specifically, the storage layer in a memristor is typically a few nanometres thick, thus even a moderate voltage drop across it can create a large enough electric field to drive the ionic processes to alter the ionic configuration of the material.…”
mentioning
confidence: 99%
“…From the outside, the device looks like a resistor, and thus offers the potential for very-high-density integration and low-cost fabrication. However, unlike a static resistor, the storage layer can be dynamically reconfigured when stimulated by electrical inputs 2,3 . This material reconfiguration leads to memory effects, where changes in physical parameters, such as the device's resistance, can be used to store data and also directly process data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[69] The switching mechanism can involve filaments or interfaces. [4] In VCM, the conductive filament is formed by oxygen-vacancy defects in oxide-based solid electrolytes, and the anion diffusion occurs within the insulating layer. ECM, also known as conductive bridging random access memory (CBRAM), requires an electrochemically active metal electrode such as Ag or Cu.…”
Section: Operation Scheme Of Rerammentioning
confidence: 99%
“…[1] Conventionally, neuromorphic engineering is based on von Neumann architecture where the processor and the memory are physically separated. Recently, solid state electronic devices were designed for neuromorphic device applications, including memristors, [3,4] new-conceptual transistors, [5,6] spin-orbit torque devices, [7] spintronic oscillators, [8] etc. In nervous system, a synapse connects two neurons, underlining signal transmitting and information processing function.…”
Section: Introductionmentioning
confidence: 99%